PENGARUH KUALITAS PENGANGGARAN DAN KOMPETENSI SUMBER DAYA MANUSIA BIDANG KEUANGAN TERHADAP KINERJA KEUANGAN SEKOLAH - SLAMET FAUZAN (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2020)
This research was conducted to identity the influence of budget quality and financial human resources competence on the school financial performance.. This research is population research. The number of population in this research is among all the vocational haigh school in Pemalang Regency with totaling 42 schools. Of the 42 schools, only 37 schools who returned the questioners. This research used quantitative approach using hypothesis testing study design. To test hypothesis using multiple linier regression analysis with the absolute different with application program SPSS. The result of analysis shows that quality of budgeting and financial human resources competence on the school have a positive significant effect on the school financial performance with simultanely or partially.